2011
DOI: 10.1177/0194599811410656
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chitinases in Hypertrophied Adenoids of Children

Abstract: The findings suggest that chitin-containing pathogens or dysregulated immune responses to them in the hypertrophied adenoids of children could be factors contributing to CRS, OME, and AR via AMCase or ChT overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Elevated or reduced AMCase levels have been reported in numerous diseases such as asthma, allergic inflammation, ocular allergy, dry eye syndrome, stomach cancer, adenoid hypertrophy, conjunctivitis, neuromyelitis, gastritis, or nasal polyp formation (Zhu et al 2004; Reese et al 2007; Bucolo et al 2008; Seibold et al 2008; Cozzarini et al 2009; Musumeci et al 2009; Park et al 2009; Bucolo et al 2011; Correale and Fiol 2011; Heo et al 2011; Nookaew et al 2013). In addition, AMCase is an important downstream effector of interleukin-13 stimulation in Th2 helper cell-mediated immune responses to pathogens, parasites and ovalbumin (Zhu et al 2004; Hartl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated or reduced AMCase levels have been reported in numerous diseases such as asthma, allergic inflammation, ocular allergy, dry eye syndrome, stomach cancer, adenoid hypertrophy, conjunctivitis, neuromyelitis, gastritis, or nasal polyp formation (Zhu et al 2004; Reese et al 2007; Bucolo et al 2008; Seibold et al 2008; Cozzarini et al 2009; Musumeci et al 2009; Park et al 2009; Bucolo et al 2011; Correale and Fiol 2011; Heo et al 2011; Nookaew et al 2013). In addition, AMCase is an important downstream effector of interleukin-13 stimulation in Th2 helper cell-mediated immune responses to pathogens, parasites and ovalbumin (Zhu et al 2004; Hartl et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the role of LPR in the presence and detectability of pepsinogen in the middle ear cavity and surface of adenoids samples is controversial. The “reverse hypothesis” considered that pepsinogen spreads from serum, becomes concentrated in the middle ear cavity, and flows toward adenoid tissues through the nasopharynx and eustachian tube . However, this presumption is difficult to address using empirical methods.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has examined the effect of adenostonsillectomy on markers of airway inflammation; we chose to explore chitinases given previous, separate findings linking them to both asthma and adenotonsillectomy (14,16). In this study, we have demonstrated that asthma control and healthcare utilization significantly improve after adenotonsillectomy and that this improvement is associated with a decrease in chitinase activity in the circulation that is not evident in children without asthma.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major chitinases in humans; chitotriosidase is a true enzyme with the ability to hydrolyze chitin, while YKL-40 is a chitinase-like protein, which has the ability to bind to chitin but not to degrade it (13). The enzymatically active chitinase, chitotriosidase (CHIT1) is overexpressed in adenoid tissue of children undergoing adenotonsillectomy with concurrent chronic rhinosinusitis, otitis media with effusion, and allergic rhinitis compared to subjects without concomitant upper airway disease (14). Additionally, proteins in the chitinase family have been demonstrated as markers of the systemic component of asthmatic disease.…”
Section: Introductionmentioning
confidence: 99%